The Dead Sea scrolls today - VanderKam, James C. (Michigan : Grand Rapids : William B. Eerdmans Publishing Company, 1994)
Summarizes the story of the Dead Sea Scrolls, their discovery, nature chronology, literary character, and background.
1. Discoveries -- 2. Survey of the manuscripts -- 3. Identification of the Qumran group -- 4. Qumran Essenes -- 5. The Scrolls and the Old Testament -- 6. The Scrolls and the New Testament -- 7. Controversies about the Dead Sea Scrolls.
Includes bibliographical references and index.
Keywords: Dead Sea scrolls; Bible. -- Criticism, Textual; Dead Sea scrolls -- Relation to the New Testament; Bible. -- Criticism, interpretation, etc; Qumran community; Essenes; Manuscripts; Israel; Palestine; Criticism, interpretation, etc